2012
DOI: 10.1373/clinchem.2011.177741
|View full text |Cite
|
Sign up to set email alerts
|

Closing the Gaps in Pediatric Laboratory Reference Intervals: A CALIPER Database of 40 Biochemical Markers in a Healthy and Multiethnic Population of Children

Abstract: BACKGROUND:Pediatric healthcare is critically dependent on the availability of accurate and precise laboratory biomarkers of pediatric disease, and on the availability of reference intervals to allow appropriate clinical interpretation. The development and growth of children profoundly influence normal circulating concentrations of biochemical markers and thus the respective reference intervals. There are currently substantial gaps in our knowledge of the influences of age, sex, and ethnicity on reference inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
301
10
9

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 400 publications
(363 citation statements)
references
References 32 publications
28
301
10
9
Order By: Relevance
“…Comparison of our 2.5th and 97.5th percentile results with findings from the CALIPER study [11] demonstrates similar reference limits and age-dependent dynamics (Figure 2). In the first 6 months of life, the upper reference limits of the two studies intersect, but those provided by us are higher than those from CALIPER for a substantial period of time.…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…Comparison of our 2.5th and 97.5th percentile results with findings from the CALIPER study [11] demonstrates similar reference limits and age-dependent dynamics (Figure 2). In the first 6 months of life, the upper reference limits of the two studies intersect, but those provided by us are higher than those from CALIPER for a substantial period of time.…”
Section: Resultssupporting
confidence: 79%
“…To ensure valid reference intervals when using indirect procedures, great care must be taken in the selection of samples and statistical algorithms. Previous evaluations of the applied algorithm [6,27] and comparison of our results to reference intervals from CALIPER, created using a direct method [11]. The x-axes are scaled differently on the left-and right-hand side of the figure to account for the dynamics in young infants; the x-axis on the right-hand side starts at 61 days.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary, two other studies reported no sex differences in children. 21,42 Both reported only CRP reference intervals (2.5th and 97.5th percentile) for broad age groups and did not investigate sex differences more closely in between. Surprisingly, in male participants of an adolescent study population even higher CRP concentrations were measured than in female participants.…”
Section: Sexmentioning
confidence: 99%
“…Амери-канской ассоциацией клинической химии (aaCC) были отработаны и представлены референтные зна-чения ЩФ в зависимости от возраста и пола, начи-ная с новорожденных детей (табл. 2) (А) [13].…”
Section: клинические рекомендацииunclassified